Strategi Pengembangan Kawasan Wisata Madakaripura dalam Pespektif Community Based Tourism (CBT) (Studi pada Dinas Kebudayaan dan Pariwisata Kabupaten Probolinggo) - Syahfudin, Mutiya (Jurnal Administrasi Publik, 2014)
Abstract: The Development Strategy of the Tourist Area of Madakaripura in Perspective of Community Based Tourism (CBT) (Studies in the Department of Culture and Tourism of Kabupaten Probolinggo). Various Indonesian tourism potential because it required a proper tourism development strategy to be able to benefit from tourism evenly.. One of the perspectives that can be used as a tourism development strategy is community based tourism (CBT). This is because in the CBT, the community became a major actors in the management and the management of a tourist area so that the application of CBT directly can also improve this aspect of the benefit of the development of tourist areas. CBT can also be applied at the Madakaripura Tours is one of the natural potential which is owned by Regency Probolinggo. Problems found from Tourist Development Agency conducted Madakaripura culture and tourism Probolinggo District which is the lack of management of tourism and the lack of adequate facilities and infrastructure.Â Therefore, expected CBT may be solving existing problems so that they can create shared well-being. Keywords: the development of tourism, Community Based Tourism (CBT), Madakaripura Waterfall. Abstrak: Strategi Pengembangan Kawasan Wisata Madakaripura dalam Pespektif Community Based Tourism (CBT) (Studi pada Dinas Kebudayaan dan Pariwisata Kabupaten Probolinggo). Indonesia memiliki potensi wisata yang beragam di setiap daerahnya. Oleh karena itu diperlukan strategi pengembangan pariwisata yang tepat untuk dapat memperoleh manfaat dari bidang pariwisata secara merata. Begitu pula yang diterapkan Dinas kebudayaan dan Pariwisata Kabupaten Probolinggo dalam pengembangan wisata Air Terjun Madakaripura. Salah satu perspektif yang dapat digunakan sebagai strategi pengembangan wisata adalah community based tourism (CBT). Hal ini dikarenakan dalam CBT, masyarakat menjadi aktor utama dalam pengelolaan dan manajeman sebuah daerah wisata sehingga penerapan CBT secara langsung juga dapat meningkatkan aspek manfaat dari pengembangan kawasan wisata. Oleh karena itu, diharapkan dengan penerapan CBT tersebut dapat menjadi penyelesaian permasalahan yang ada sehingga dapat menciptakan kesejahteraan bersama. Â  Kata kunci: pengembangan wisata, Community Based Tourism (CBT), Air Terjun Madakaripura.Â